2015
DOI: 10.5539/ass.v11n12p11
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior and Bank Profitability: Examining relationships in an Iranian Bank

Abstract: Organizational citizenship behavior is an individual and voluntary behavior that is not designed directly by formal reward system. Nevertheless, it causes increase in effectiveness and efficiency of organizational performance. This study aims to evaluate and analyze relationship between organizational citizenship behavior and profitability of branches of Mellat Bank in Kerman Province in Iran. Sample consists of all employees of Mellat Bank branches in Kerman Province that work in 87 branches of Kerman Provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…OCB as an unique behavior could provide with different colors for the organization, through its extra behaviors that are shown as voluntarily act to provide additional benefits fot the organization (Podsakoff et al, 2000). Through its extra behavior shown by employees, it also provides hegemony in particular behavior within the organization that could also lead to better productivity performance, and even better financial profitability of the organization (Nawaser et al, 2015). Several studies that have been conducted on the role of antecedents originating from employees' within to enhance OCB have been conducted, for example, the role of employees' motivation towards OCB (Febriani and Saleh, 2019;Kumar and Prabakar, 2016;Hasanah and Suriansyah, 2019); individual job satisfaction towards OCB (Musringudin et al, 2017;Saxena et al, 2019;Prasetio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…OCB as an unique behavior could provide with different colors for the organization, through its extra behaviors that are shown as voluntarily act to provide additional benefits fot the organization (Podsakoff et al, 2000). Through its extra behavior shown by employees, it also provides hegemony in particular behavior within the organization that could also lead to better productivity performance, and even better financial profitability of the organization (Nawaser et al, 2015). Several studies that have been conducted on the role of antecedents originating from employees' within to enhance OCB have been conducted, for example, the role of employees' motivation towards OCB (Febriani and Saleh, 2019;Kumar and Prabakar, 2016;Hasanah and Suriansyah, 2019); individual job satisfaction towards OCB (Musringudin et al, 2017;Saxena et al, 2019;Prasetio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, organisational citizenship behaviour was a significant mediator between the two dimensions of empowerment (structural and psychological) and organisational performance, similar to Kariuki and Kiambati (2017). Due to the significant role of OCB, the literature suggested that it should be promoted in organisations because of its effect on profitability and organisational performance (Nawaser, Ahmadi, Ahmadi & Dorostkar, 2015). It is also necessary to mention that including the employees in decision-making in the day-to-day administration has a link with employee motivation to engage in citizenship behaviour (Khoshnammoghadam, 2017) and performance as well.…”
Section: Theoretical Implicationsmentioning
confidence: 75%
“…Organ (1997) argued that instead of only assuming organizational citizenship behavior (OCB) as an extrarole behavior, a conduct beyond the job or as an unrewarded behavior, OCB should be redefined with a new definition. Nawaser et al (2015) describe OCB as a random and extrarole behavior that improves organizational efficiency and is not directly or indirectly regulated by an organization's official reward system. OCB has become one of the most important behaviors for a person to own.…”
Section: Introductionmentioning
confidence: 99%